Information Systems Study on the Production System of Cejogua Sports Corporation - Alaan, Ailene B. (College of Engineering, 1996)
Industrial Engineering 154 introduces concepts in the field of Information Systems. This study is an academic exercise which provides a venue for the students of the course to apply and appreciate various tools and techniques in the analysis and design of Information Systems. The site of the group for this project study is Cejogua Sports Corporation, which carries the brand name BOTAK PasadyaTM. It is located at #131 Kamuning Road, Quezon City. It manufactures different types of sportswear and sport accessories for different types of sports enthusiasts. All products may be either a job order or a product line. Its vision is to be a visible figure in sports, in general and in running in particular.